Can Biomarkers of Oxidative Stress in Serum Predict Disease Severity in West Nile Virus Infection? A Pilot Study - Maxim Van Herreweghe; Annelies Breynaert; Tess De Bruyne; Corneliu Petru Popescu; Simin-Aysel Florescu; Yaniv Lustig; Eli Schwartz; Federico Giovanni Gobbi; Nina Hermans; Ralph Huits (Tropical Medicine and Infectious Disease, 2022)
West Nile virus (WNV) can cause asymptomatic infection in humans, result in self-limiting febrile illness, or lead to severe West Nile Neuroinvasive disease (WNND). We conducted a pilot study to compare selected biomarkers of oxidative stress in sera of viremic West Nile virus patients and asymptomatic infected blood donors to investigate their potential as predictors of disease severity. We found that total oxidant status was elevated in WNND and in uncomplicated WNV infections (median 9.05 (IQR 8.37 to 9.74) and 7.14 (7.03 to 7.25) µmol H2O2 equiv./L, respectively) compared to asymptomatic infections (0.11 (0.07 to 0.19) µmol H2O2 equiv./L) (p = 0.048). MDA levels showed a similar trend to TOS, but differences were not significant at α = 0.05. Total antioxidant status did not differ significantly between different disease severity groups. Oxidative stress appears to be associated with more severe disease in WNV-infected patients. Our preliminary findings warrant prospective studies to investigate the correlation of oxidative stress with clinical outcomes and severity of WNV infection.